ANALISIS KEBUTUHAN RUANG PARKIR FKIP UNIVERSITAS LAMBUNG MANGKURAT BANJARMASIN - Menik Susilowati; Deasy Arisanty; Sidharta Adyatma (JPG (Jurnal Pendidikan Geografi), 2015)
Lambung Mangkurat university is the eldest University at Kalimantan. This university stand on  September 21th 1958, but can be formalized on November 1st 1960, and standing until now. The perpove of this study is to know the requirement and room capacity park at Faculty of teachers training and Education UNLAM Banjarmasin's City have sufficed or not. The result of this study can be that analysis that  :  the supreme Accumulated parking is happening for motorbike in FKIP 1, as much as 511 unit, whereas for car as much as 11 unit, that is happening between hour 15.10 16.10 Wita. The supreme accumulated parking thatis happening for motorbike in FKIP 2, as much as 1.446 unit between hour 07.35 08.35 Wita.  The supreme durasi of parking that happen in parking FKIP 2 as much as 143,33 minutes / vehicles.  The supreme of alternation parkir’s level happen in FKIP 1 for car as much as 4,63 vehicles / SRP Per minute.  The supreme capacity park is capacity park for motorbike in FKIP 1 as much as 53,02 SRP Per minute, where is the slot’s sam that available as much as 2.651 whit the average long park as much as 0,05 minutes / vehicles. The supreme of index park is inden park motorbike as much as 215, 18 that happen in FKIP 2. The recessity room or the augmentation of extent room park for motorbike in FKIP 1 is 1.738  m², for car is 586,5 m², and FKIP 2 for motorbike is 1.503 m² and for car is 372 m².Key word  : Accumulate park, The duration of park, Capacity of park, Index park and the necessity room park FKIP UNLAM Banjarmasin City